Đề xuất khung kĩ thuật về thiết kế công cụ đánh giá phẩm chất và năng lực theo Chương trình giáo dục phổ thông 2018 - Đặng , Xuân Cương; Nguyễn , Thị Hương; Nguyễn , Tất Thắng (Tạp chí Giáo dục, 2024)
With the trend of innovating curriculum development from a content approach to a competency approach, the relationship among curriculum, teaching, and assessment needs to be given proper attention. Teaching and assessment are two parallel activities, in which assessment provides reliable and valuable information to serve teachers’ teaching and students’ learning. In the challenges of implementing many different sets of textbooks, assessment plays an important role in providing information for implementation according to the regulations and requirements in the approved curriculum. The article proposing a theoretical framework for developing instrument to assess characters and competencies according to the 2018 curriculum, which proposes the types of instruments that can be used, provides corresponding types of instruments for formative assessment and summative assessment of characters, general and domain-specific competencies as well as the process of designing and using instruments for each type of assessment. This framework provides detailed instructions that teachers can apply in the process of teaching their subjects and educational activities.